LAWMAKING POLICY AS INNOVATIVE DIRECTION OF FUNDAMENTAL RESEARCH IN LAW - Andrei P. Mazurenko (Современная наука и инновации, 2022)
The problems of such an innovative research areas of common law as law-making policy.Analyzes the multiple perspectives of scientists on different approaches to understanding the nature and content of the political and legal phenomenon. Conclusions, grounded in fundamental research and the relevance of further law-making policy. Offered a number of definitions copyrights considered in the paper of scientific concepts.